Perancangan Animasi Interaktif Prosedur Merawat Peralatan Multimedia pada Jurusan Multimedia SMK BPS&K II Bekasi - Soleh, M Rizki; Nurajizah, S; Muryani, S (Program Studi Sistem Informasi, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2019)
Media is often used in conveying procedural information to users. In the world of education media is used to convey a knowledge in the teaching and learning process called learning media. In the world of education a learning method can be presented using learning aids. But sometimes the props used are still less attractive because they are less interactive and monotonous. In this discussion students who use multimedia equipment still do not understand the procedures in terms of maintain. So it is important to build a desktop-based interactive animation media design in delivering information about the maintenance procedures for multimedia tools before practicum is carried out. So that students can understand and remember the procedures for maintaining equipment when using it. In making this interactive animation using the waterfall method so that in the making stage easier to understand and the development model can be understood the logic of the running system. The result is that with the implementation of this interactive animation media students can easily understand and remember maintenance that must be taken on multimedia equipment, through the illustrations provided in the form of animations to describe the treatment procedures.